2021
DOI: 10.5336/nurses.2020-77350
|View full text |Cite
|
Sign up to set email alerts
|

Assesment of Anxiety Levels of Mothers Whose Babies are Hospitalized in Neonatal Intensive Care Unit

Abstract: Yenidoğan dönemi, doğumdan sonraki ilk 28 günü içerir. Bebeğin gerçek dünya ile ilk kez tanıştığı ve uterus dışındaki yaşama uyum sağlamaya çaba gösterdiği, hayatın en riskli ve en zor, dolayısıyla da en belirleyici dönemini kapsamaktadır. 1,2 Bu dönem sadece annenin değil, ebeveyn sağlığının korunması ve geliştirilmesi açısından da önemli bir dönemdir. Ayrıca bu dönem, hızlı olmakla birlikte karmaşık bir

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 7 publications
1
1
0
Order By: Relevance
“…In the present research, no significant difference was found in perceived stress levels with respect to whether the pregnancy was planned or not. Similarly to this result, Omak et al(2021) reported that there was no difference between the state of wanting pregnancy and anxiety levels among mothers with their babies in the neonatal unit (20). The results of the present study showed that perceived stress levels were higher among non-working mothers.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In the present research, no significant difference was found in perceived stress levels with respect to whether the pregnancy was planned or not. Similarly to this result, Omak et al(2021) reported that there was no difference between the state of wanting pregnancy and anxiety levels among mothers with their babies in the neonatal unit (20). The results of the present study showed that perceived stress levels were higher among non-working mothers.…”
Section: Discussionsupporting
confidence: 84%
“…Özyazıcıoğlu and Güdücü Tüfekci (2010) found no significant difference in state and trait anxiety levels with respect to the education level of mothers whose babies were hospitalized in the neonatal unit (20,21). Musabirema et al (2015) found that among mothers whose babies were hospitalized in the neonatal unit, perceived stress levels in terms of the appearance and sounds of the neonatal unit were higher in primary school graduates compared to university graduates (22).…”
Section: Discussionmentioning
confidence: 99%